Kava and its Kavalactones Inhibit Norepinephrine-induced Intracellular Calcium Influx in Lung Cancer Cells - Botello, Jordy F.; Corral, Pedro; Bian, Tengfei; Xing, Chengguo (Planta Medica, 2020)
Kava, the extract of the roots of Piper methysticum, has been traditionally consumed in the South Pacific islands for its natural relaxing property. Epidemiological data suggests that kava consumption may reduce human cancer risk, and in vitro and in vivo models suggest chemopreventive potential against carcinogen-induced tumorigenesis. Therefore, knowledge about its molecular mechanisms and responsible ingredient(s) for these beneficial properties will better guide kavaʼs use for the management of these disorders. Psychological stress typically results in increased production of stress hormones, such as norepinephrine (NE), which activate adrenergic receptors (ARs). Psychological stress has also been associated with increased cancer incidence and poor clinical outcomes in cancer patients. Mechanistically, binding of NE to ARs induces intracellular calcium influx, which activates downstream signaling pathways involved in both stress and cancer development. In this study, we characterized the effect of kava and its components, 3 fractions and 6 major kavalactones, on NE-induced intracellular calcium influx in H1299, a human non-small cell lung carcinoma cell line. Results show that kava extract effectively inhibits NE-mediated intracellular calcium influx in H1299 cells, potentially through antagonizing β-AR signaling. This inhibitory activity is recapitulated by the major kavalactones in kava. Among the 6 major kavalactones, DHK demonstrated the best potency. Taken together, our study suggests a novel mechanism through which kava and its ingredients potentially offer the anxiolytic and cancer-preventive activity.
Keywords: kava; kavalactones; stress; cancer prevention; norepinephrine; calcium; Piper methysticum; Piperaceae